The Effect of Using Podcasts as a Learning Medium on Improving Student Learning Outcomes and Communication Skills - Rezi Munthe, Debi; Rizka Harfiani; Juli Maini Sitepu (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
The use of podcasts in Islamic Religious Education remains minimal, especially at the junior high school level. Many children find learning with infrequently changing media boring. Most Islamic Religious Education teachers still rely on the lecture method as their primary approach, with limited and less varied use of learning media. This situation has implications for low student engagement and interest in learning, particularly because Islamic Religious Education material is often perceived as abstract and overly theoretical. The purpose of this study was to determine how the use of podcasts as a learning medium impacts students' learning outcomes in Islamic Religious Education at SMP Negeri 1 Sitinjo and their ability to communicate. This study employed a quantitative methodology and a quasi-experimental pretest-posttest control group design. Two classes participated in this design: an experimental class using podcasts and a control class using conventional methods. The questionnaires on learning outcomes and communication skills of the study were tested for validity and credibility. To analyze the data, MANOVA, ANCOVA, and independent t-tests were used, and SPSS was used. The results showed that podcasts significantly influenced students' learning outcomes and communication skills, with a partial eta squared value of 0.564. Therefore, podcasts are considered an innovative learning option that encourages active student participation, improves material understanding, and enhances their communication skills in Islamic Religious Education learning in the digital era.